The Relationship Between Attachment and Love Style with Self Confidence in Students in Village - Lilik Mauludiyah; Ramon Ananda Paryontri (Universitas Muhammadiyah Sidoarjo, 2023)
Students begin to act on their own decisions, experience changes such as lack of confidence such as always comparing themselves with others and being afraid to have opinions. The purpose of this study was to determine the relationship between attachment style and self-confidence and the relationship between love and self-confidence in students in Bangil Village. This research uses correlational quantitative research. This research was conducted in Bangil with a population of 321 students. The sample in the study amounted to 172 students who were taken by accidental sampling technique. The measuring instrument used for data collection uses an attachment style scale adapted from Nabila's research (2018), a love scale adapted from Hidayatullah's research (2018) and a self-confidence scale adapted from Anggia's research (2020). Data analysis using Pearson product moment correlation using SPSS 21 for windows program. The results of the analysis showed a correlation score of r = 0.482 with a significance of 0.000 (p<0.05) between attachment style and self-confidence, which means the first hypothesis is accepted. Thus, there is a significant positive relationship between attachment style and self-confidence. The results of data analysis showed a correlation score of r = 0.645 with a significance of 0.000 (p<0.05) between love and self-confidence, which means that the second hypothesis is accepted. Thus, there is a significant positive relationship between love and self-confidence. The contribution of the attachment variable to self-confidence is 23.2%, while the contribution of the love variable to self-confidence is 41.7%.